Digital Banking and Operational Efficiency toward Bank Sustainability Performance - Soleman Lenggu, Max ABR.; Muhtarom, Muhtarom; Rangi, Noah; Sunengsih, Meriyana (ADI Journal on Recent Innovation (AJRI), 2026)
The rapid growth of digital banking has significantly transformed banking operations by enhancing efficiency and supporting sustainability-oriented practices aligned with the Sustainable Development Goals (SDGs), yet empirical evidence on its integrated impact remains limited, particularly in emerging markets. This study aims to examine the effect of digital banking adoption on operational efficiency and bank sustainability performance, while assessing the role of efficiency in strengthening sustainable outcomes. A quantitative panel data approach is applied using multi-year data from 25 commercial banks over the period of 2018–2023, where digital banking indicators, efficiency measures, and sustainability performance proxies are analyzed through regression-based panel data models with appropriate control variables. The empirical findings reveal that digital banking adoption positively and significantly improves operational efficiency, and higher efficiency levels are associated with enhanced sustainability performance, indicating that efficiency serves as a key mechanism linking digital transformation and sustainable banking performance. This study concludes that digital banking acts as a strategic enabler of sustainable banking by simultaneously improving operational efficiency and long-term sustainability performance, offering important implications for bank managers and policy makers in formulating data-driven digital transformation strategies that support sustainable financial development.